(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the pilot-scale filtration process in the pre-treatment of landfill leachate through physical-chemical analyzes. Four types of filters were evaluated; in which the filtering materials used were sand, medium and coarse sand, activated carbon, clay, gravel n ° 0 and gravel n ° 1. Statistical analysis was performed by analysis of variance (ANOVA) followed by the Tukey test, when applicable. Data were expressed as mean ± standard deviation and P values ​​<0.05 were considered statistically significant. The pH did not show a reduction and a significant increase of the filter analyzes when compared to the crude leachate, the electrical conductivity obtained a significant reduction in filter 1 (p <0.001), 2 and 4 with p <0.05 when compared to the crude leachate. In dissolved oxygen, there were significant increases in filter 1 and 2 (p <0.001) and in filter 4 (p <0.01). According to the reduction of the parameters, we can observe that the filter 1 reduced approximately 50% of the electrical conductivity and obtained an increase of 377,75% in the dissolved oxygen, being these the greater values ​​of reduction and increase of the parameters. The flow of the filters was all different, in which the filter 4 obtained higher flow and the filter 3 with the lower flow. According to the analysis of the results, the filter considered the most feasible in relation to the flow and with the analysis of the parameters was the filter 1.